Invigorating the City of Holstebro - Christoffersen, Erik Exe (Peripeti, 2017)
The Ship Bridge (1991) was a collaboration with Odin Teatret. It took place on a parking lot on the roof of a supermarket in the middle of Holstebro, a city with some 50,000 inhabitants in west Denmark.